POTENTIAL FOR IMPLEMENTING BIOLOGY LEARNING BASED ON THE QUR’AN IN HUMAN REPRODUCTIVE SYSTEM MATERIAL - Asna Nofiyanti; Dewi, Endah Rita Sulistya; Hayat, M.Syaipul; Roshayanti, Fenny (LPPM Universitas PGRI Semarang, 2025)
When entering adolescence, physical growth and sexual maturation occur, if not equipped with positive values, it will have an impact such as free sex. The phenomenon of free sex is increasing due to the lack of understanding of the human reproductive system and religious values. The effort to overcome this is by integrating biology learning on the concept of human reproductive system with the values contained in the Qur'an. The purpose of this study is to analyse the potential application of Qur'an-based biology learning on human reproductive system. The type of research used is descriptive qualitative with a sample of MGMP biology teachers in Mranggen sub-district using random sampling method. Supporting data sources came from the opinions of students, teachers and Head of Madrasah at MTs Al Furqon. The data collection techniques used were questionnaires, observations and interviews. Descriptive analysis technique was used to describe the implementation potential. With a percentage of 100%, teachers think there is potential for Qur'an integration on human reproductive system lesson. From the results of the questionnaire, with a percentage of 80%, teachers think there is potential to implement Qur'an-based biology learning on human reproductive system for madrasah students. The results of observations on teachers, students, madrasah head and infrastructure at MTs Al Furqon show that there is potential to implement Qur'an-based biology learning on human reproductive system lesson. It is hoped that later it can also be implemented to other biological concepts.